Plankton diversity around Sempu Strait, Indonesia, revealed by eDNA metabarcoding - DIAN ALIVIYANTI; SHAFIRA HAPSARI NOOR AMALIA; MUHAMMAD DAILAMI; ASEP AWALUDIN PRIHANTO; SYARIFAH HIKMAH JULINDA SARI; HEDER DJAMALUDIN; EKWAN NOFA WIRATNO (Society for Indonesian Biodiversity, 2025)
Abstract. Aliviyanti D, Amalia SHN, Dailami M, Prihanto AA, Sari SHJ, Djamaludin H, Wiratno EN. 2025. Plankton diversity around Sempu Strait, Indonesia, revealed by eDNA metabarcoding. Biodiversitas 26: 5848-5856. Plankton diversity plays a critical role in assessing marine ecosystem health and productivity. Environmental DNA (eDNA) metabarcoding offers a highly informative tool for detecting plankton biodiversity more comprehensively compared to conventional methods. This study assessed plankton diversity and water quality in the Sempu Strait, Indonesia, by analyzing eDNA samples collected from five stations during a single sampling period in August 2024. Environmental parameters (temperature, salinity, pH, dissolved oxygen, nitrate, and phosphate) were measured and found within typical ranges, except for nitrate and phosphate, which exceeded marine quality thresholds. Water samples were filtered and amplified using the 18S V9 region, and sequences were processed using DADA2 and assigned taxonomically against the PR2 database. A total of 361 species across 341 genera were identified from 2.8 million raw reads. The Shannon-Wiener index (H') diversity indices range from 4.61 to 6.43, while Simpson's index (D) ranges from 0.964-0.997, indicating overall high alpha diversity. The most dominant phytoplankton genera were Leptocylindrus and Chaetoceros, while Neocalanus dominated the zooplankton community. Stations near anthropogenic activity showed distinct taxonomic profiles and higher nutrient concentrations. These findings confirm that eDNA metabarcoding is an effective and sensitive approach for monitoring marine plankton communities. This method enhances biodiversity detection and provides valuable reference for future ecological assessments and conservation planning in Indonesian coastal ecosystems.